N′-[(E)-1-(5-Bromo-2-hydroxyphenyl)ethylidene]-2-chlorobenzohydrazide - Chang, Jian-Guo (International Union of Crystallography, 2011)
The title compound, C(15)H(12)BrClN(2)O(2), was synthesized by the condensation of 1-(5-bromo-2-hydroxyphenyl)ethanone with 2-chlorobenzohydrazide in anhydrous ethanol. The Schiff base molecule displays a trans configuration with respect to the C=N double bond. The dihedral angle between the two benzene rings is 13.74 (3)°. The molecular conformation is stabilized by an intramolecular O—H⋯N and the crystal structure by intermolecular N—H⋯O hydrogen bonds.